Network bandwidth forecast method for IMS business in power dispatching communication - Xiande BU; Zhenhua QU; IBinglin L; IANWenfeng T (Dianxin kexue)
The electric power dispatching data network business requirements of the IMS system were analyzed,the networking of the dispatching data network method was proposed,and the amount of the dispatching data network users was researched.According to the technology development and the power communication services requirement,IMS technique was used to construct next generation communication system,and the electric power dispatching data network was needed to be designed to load IMS services.The calculation method of network bandwidth and multimedia business traffic model for loading multimedia businesses was studied.It has guiding significance to construct next generation communication network for smart grid.